PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KERAGAMAN ALAM INDONESIA SISWA KELAS VIII-F SMP NEGERI 18 SURABAYA TAHUN PELAJARAN 2024-2025 - Qurrota A'yun, Shauma; Rindawati; Ririn Fatayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The effectiveness of education in schools is highly dependent on student engagement and the utilization of appropriate pedagogical frameworks. Learning models play an important role in the teaching and learning process because they have the ability to capture students' attention, stimulate their interest, and foster their active participation. Cooperative learning in the Teams Games Tournament format is a pedagogical approach that is easy to implement, involves students as peer educators, and incorporates game elements. This study used Classroom Action Research (CAR) as a strategy to overcome the challenges faced. The data collection procedures used included observation, testing, and documentation. The test was given in the form of a post-test, consisting of multiple-choice questions. The data analysis methodology used included qualitative and quantitative data analysis. During cycle I, out of 33 students in class VIII-F of SMP Negeri 18 Surabaya, 14 students were classified as complete, accounting for 42.42% of the total, while 19 students were classified as incomplete, accounting for 57.57%. In cycle II of 33 students, 26 students, covering 78.78% of the total, were classified in the complete category because they successfully completed the Learning Target Achievement Criteria (KKTP) with a score of ≥78. A total of 7 students, covering 21.21% of the group, were classified as incomplete because they failed to achieve the Learning Target Achievement Criteria (KKTP), which requires a score of ≤78. Therefore, this study shows that the use of the Teams Games Tournament cooperative learning paradigm can improve student.